Health care costs of home care enzyme replacement therapy for patients with lysosomal storage diseases in Germany - Ria Heinrich; Franziska Claus; Tonio Schoenfelder (Orphanet Journal of Rare Diseases)
Abstract Background Lysosomal storage diseases (LSDs) can be treated with intravenous enzyme replacement therapy (ERT). ERT is being administered either in specialized clinics or in the home care setting. Studies indicate that home-based ERT can be considered safe and positively effects patient reported outcomes. Due to the higher level of individual care required by nurses when administering ERT at home, questions arise whether this will result in additional costs for health care systems. Since cost data to the German health care system are currently unavailable, this study aims to assess home care ERT costs of LSD patients. Methods The longitudinal study assessed the direct costs of home-based ERT for patients with LSD diseases Fabry, Pompe, Gaucher, and MPS I from 2019 to 2021 on a patient-by-patient basis by evaluating the healthcare documentation. Costs assessed included ERT drug and further administration equipment, time needed to prepare, administer, and post-process the infusion, and travel expenses of nursing staff. Results Data from 62 patients was analyzed: of these, 29 (46.8%) with Fabry disease, 19 (30.6%) with Pompe disease, 10 (16.1%) with Gaucher disease, and 4 (6.5%) with MPS I. Patients ranged in age from 3 to 79 (mean 40 years); 42% of patients reported comorbidities (19.4% with hypertension, and 10% with heart disease). Mean total ERT-related costs were €369,047 per year across all patients. Approximately 98.5% of these costs were attributable to the infusion therapy and administration itself (€363,880), and approximately 1.5% were attributable to personnel and travel costs. Patients with Pompe disease incurred the highest average annual costs (€483,907) and patients with Fabry disease the lowest (€264,896). Cost differences among underlying LSDs were due primarily to ERT drug costs; the drug infused for Fabry disease costs about half as much as that for Gaucher or for Pompe disease. Despite MPS I patients requiring about twice as many infusions, significantly lower drug costs for this disease resulted in the second lowest total mean costs of all LSD subtypes analyzed. Conclusion As total costs are almost entirely driven by infusion-related material, especially the ERT drug, moving ERT into the home environment is not expected to increase costs.